1996
DOI: 10.1207/s15327558ijbm0302_3
|View full text |Cite
|
Sign up to set email alerts
|

Relations among night work, dietary habits, biological measures, and health status

Abstract: A cross-sectional study was conducted to investigate dietary intake, behavioral habits, and clinical and metabolic differences in night workers compared to day workers and to evaluate the metabolic differences associated with diet and body habits that occur between these two groups. Dietary habits, biological parameters, and health status were collected in 1,200 night workers and in an equal number of day workers, matched for gender, age, and socioeconomic status. Our findings demonstrated that night workers h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
68
2
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(72 citation statements)
references
References 13 publications
1
68
2
1
Order By: Relevance
“…In contrast to our finding of a higher energy intake among shift compared to day workers, the majority of previous studies observed no significant differences (15,17,19,24,39,40). However, three of these studies observed a statistically non-significantly higher energy intake among shift compared to day workers (24,39,40).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast to our finding of a higher energy intake among shift compared to day workers, the majority of previous studies observed no significant differences (15,17,19,24,39,40). However, three of these studies observed a statistically non-significantly higher energy intake among shift compared to day workers (24,39,40).…”
Section: Discussioncontrasting
confidence: 99%
“…Significant associations (at P<0.05) are printed in bold. studies was insufficient to make proper inferences about differences in energy intake between groups since these studies had a small sample size (N=25-396) (19,24,39,40) and/or did not adjust for potential confounders such as age, gender and socioeconomic status (15,17,19,24,39,40). In addition, we observed that BMI and waist circumference were only slightly higher among shift compared to day workers, suggesting that energy balance was not strikingly different.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Responses were coded in three categories (irregular, Ͻ1 hour of walking per day, Ն1 hour of walking per day) (20). Alcohol intake was estimated in grams of alcohol per day, from a short validated semiquantitative dietary questionnaire (21).…”
Section: Assessment Of Sociodemographic and Behavior Characteristicsmentioning
confidence: 99%